Gastrointestinal stromal tumor presenting with spontaneous tumor rupture and intratumoral hemorrhage: A rare encounter - Swapnil Sen; Nibedita Sen; Ishita Laha; Achintya Kumar Das (Indian Journal of Case Reports, 2021)
Gastrointestinal stromal tumors (GISTs) are typically benign tumors that most commonly occur along the GI tract. Most commonly, patients with these tumors present with GI bleeding, which may present as an acute bleed with melena or hematochezia. GISTs presenting with spontaneous tumor rupture and intratumoral hemorrhage leading to hemoperitoneum is an uncommon complication. We report an atypical presentation of a GIST presenting with tumor rupture and intratumoral hemorrhage in an 81-year-old gentleman, who presented with heaviness in the left side of the upper abdomen for the past 3 weeks associated with anorexia and fullness after meals. On clinical examination, an intra-abdominal intraperitoneal mobile lump was palpable in the left upper quadrant approximately 7.5 cm in diameter, firm in consistency, moving with respiration which spontaneously ruptured 2 days before the planned elective operation. Emergency exploratory laparotomy with wide local excision had to be undertaken.